Renoprotection Induced by Aerobic Training Is Dependent on Nitric Oxide Bioavailability in Obese Zucker Rats. (28th September 2021) - Neves, Rodrigo Vanerson Passos; Corrêa, Hugo de Luca; de Sousa Neto, Ivo Vieira; Souza, Michel Kendy; Costa, Fernando; Haro, Anderson Sola; Deus, Lysleine Alves; Reis, Andrea Lucena; Simões, Herbert Gustavo; Andrade, Rosângela Vieira; Assumpção, Cláudio Oliveira; Stone, Whitley; et al.
Abstract : Aerobic training (AT) promotes several health benefits that may attenuate the progression of obesity associated diabetes. Since AT is an important nitric oxide (NO - ) inducer mediating kidney-healthy phenotype, the present study is aimed at investigating the effects of AT on metabolic parameters, morphological, redox balance, inflammatory profile, and vasoactive peptides in the kidney of obese-diabetic Zucker rats receiving L-NAME (N(omega)-nitro-L-arginine methyl ester). Forty male Zucker rats (6 wk old) were assigned into four groups (n = 10, each): sedentary lean rats (CTL-Lean), sedentary obese rats (CTL-Obese), AT trained obese rats without blocking nitric oxide synthase (NOS) (Obese+AT), and obese-trained with NOS block (Obese+AT+L-NAME). AT groups ran 60 min in the maximal lactate steady state (MLSS), five days/wk/8 wk. Obese+AT rats improved glycemic homeostasis, SBP, aerobic capacity, renal mitochondria integrity, redox balance, inflammatory profile (e.g., TNF- α, CRP, IL-10, IL-4, and IL-17a), and molecules related to renal NO - metabolism (klotho/FGF23 axis, vasoactive peptides, renal histology, and reduced proteinuria). However, none of these positive outcomes were observed in CTL-Obese and Obese+AT+L-NAME (p < 0.0001 ) groups. Although Obese+AT+L-NAME lowered BP (compared with CTL-Obese; p < 0.0001 ), renal damage was observed after AT intervention. Furthermore, AT training under conditions of low NO - concentration increased signaling pathways associated with ACE-2/ANG1-7/MASr. We conclude that AT represents an important nonpharmacological intervention to improve kidney function in obese Zucker rats. However, these renal and metabolic benefits promoted by AT are dependent on NO - bioavailability and its underlying regulatory mechanisms.